2021
DOI: 10.30880/ijie.2021.13.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eggshell and Natural Chloride Stabilized Soil Using Geophysical Techniques

Abstract: Although many techniques are available for the evaluation of soil parameters, but a quick and efficient method is always welcome. To avoid the hassle calculation and tedious procedures of testing; practitioners seek a fast method for site implementation of laboratory results. In the recent era of development and technology, it has been necessary to adopt the advanced techniques to evaluate the geotechnical parameters. In the present study, correlations between geophysical and compaction tests results have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recently, pozzolans from waste materials such as fly ash, rice husk ash, and slag are considered eco-friendly cementitious materials that can replace traditional materials such as OPC [4]- [9]. Various admixtures such as cement, fly ash, lime, blast-furnace slag cement, alkaline activation, eggshell powder, sodium chloride, polypropylene fiber, and calcium chloride were used in different areas in the world [6], [7], [10]- [17]. Recently, Tran et al [18] investigated the cement -DZ33 treated soil at a site for a rural road in Vietnam and concluded that the treated soil had been improved significantly, including elastic modulus of reinforced soil, splitting tensile strength, compressive strength, and California Bearing Ratio (CBR).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pozzolans from waste materials such as fly ash, rice husk ash, and slag are considered eco-friendly cementitious materials that can replace traditional materials such as OPC [4]- [9]. Various admixtures such as cement, fly ash, lime, blast-furnace slag cement, alkaline activation, eggshell powder, sodium chloride, polypropylene fiber, and calcium chloride were used in different areas in the world [6], [7], [10]- [17]. Recently, Tran et al [18] investigated the cement -DZ33 treated soil at a site for a rural road in Vietnam and concluded that the treated soil had been improved significantly, including elastic modulus of reinforced soil, splitting tensile strength, compressive strength, and California Bearing Ratio (CBR).…”
Section: Introductionmentioning
confidence: 99%